INADEQUATE DEPRECIATION METHODS. - Saliers, E. A. (The Accounting Review, 1937)
Abstract Perhaps no topic has been the subject of such wide differences of opinion as the method used, under given conditions, to make allowance for the expense which results from the disappearance of value of physical assets, commonly termed depreciation. These methods vary from those which result in a minimum charge to those which result in a maximum charge for any given period. Absolute uniformity in this respect is neither attainable nor desirable. Allowance must always be made for natural differences arising from geographical location, climate, and the character of the asset in question. Neither can the differences of opinion of individuals be entirely erased. Depreciation will long continue to be a controversial subject. By recognised opinion, however, much that is erroneous or dangerous may be eliminated from the list of proposed procedures. Methods which may be condemned are those which, if persisted in, result in financial embarrassment or bankruptcy as well as in gross inequality in treatment of the various parties interested in the progress of the enterprise.